2012
DOI: 10.1016/j.biortech.2011.10.069
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas reductions through enhanced use of residues in the life cycle of Malaysian palm oil derived biodiesel

Abstract: This study identifies the potential greenhouse gas (GHG) reductions, which can be achieved by optimizing the use of residues in the life cycle of palm oil derived biodiesel. This is done through compilation of data on existing and prospective treatment technologies as well as practical experiments on methane potentials from empty fruit bunches. Methane capture from the anaerobic digestion of palm oil mill effluent was found to result in the highest GHG reductions. Among the solid residues, energy extraction fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 9 publications
1
27
1
Order By: Relevance
“…Many of the technical options (e.g. biogas, mulching) are widely applied in modern plantations and mills in Asia Poh & Chong 2009;Hansen et al 2012;Heriansyah 2012;Kaewmai et al 2013;Yoshizaki et al 2013) and have also been proven to be cost-effective, for instance because they lead to increased electricity production (biogas) or reduced need for fertilizers (e.g. mulching).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the technical options (e.g. biogas, mulching) are widely applied in modern plantations and mills in Asia Poh & Chong 2009;Hansen et al 2012;Heriansyah 2012;Kaewmai et al 2013;Yoshizaki et al 2013) and have also been proven to be cost-effective, for instance because they lead to increased electricity production (biogas) or reduced need for fertilizers (e.g. mulching).…”
Section: Discussionmentioning
confidence: 99%
“…The type of mulching depends on plantations characteristics (in particular soil conditions and age of the palm). For instance, if there are immature palms (1-3 years) the EFB should be spread out 0.2-1.5 m away from the palm base (Hansen et al 2012;Heriansyah 2012). During the mill visits, no dumped EFB was observed in the C-RSPO mills.…”
Section: Palm Oil Mills -Wastewater and Empty Fruit Bunch Managementmentioning
confidence: 99%
“…As per the global index, more than one-third of vegetable oil production is achieved by the processing of oil palm fruit together with other wastes including palm oil mill effluent (POME), empty fruit bunches (EFB), palm pressed fibre (PPF), as well as palm kernel shell (PKS) (Madaki and Seng 2013). In addition to it, disposal of these wastes without any proper treatment causes harmful impacts to the environment (Hansen et al 2012). It is also found that POME contains high organic content (80,000 mg/L COD) (Abdurahman et al 2011) along with water soluble and suspended materials (palm fibre and oil residues).…”
Section: Introductionmentioning
confidence: 98%
“…Malaysia and Indonesia are the two major palm oil producing countries, covering more than 85% of the world's total supply (Hansen et al 2011;Umar et al 2014). Hence, a tremendous amount of sustainable and renewable raw material exists in these two countries.…”
Section: Introductionmentioning
confidence: 99%
“…Malaysia alone was forecasted to have higher than 40% of the material in 2015 (Sumathi et al 2008). From 2005 to 2009, palm oil plantation coverage reached about 14% of the total land area in the country, with an average growth rate of 3.9% (Hansen et al 2011). Such an ample and sustainable resource for renewable energy could be used for bringing renewable energy to the mainstream energy supply in Malaysia (Mohammed et al 2010;Chang 2014).…”
Section: Introductionmentioning
confidence: 99%